"I" and "others" in Raboni's poetry: From Le case della Vetra to Cadenza d'inganno (ENTHYMEMA, 2020)
This article intends to examine the relationship between the lyric ego and the other individuals in Raboni’s first two collections of poems, Le case della Vetra and Cadenza d’inganno, against the background of the weakening process of the poetic “I” which occurred around the 1960s. The aim is to show how the Milanese poet progressively opens the space of his texts to other characters’ speech in order to create a new type of lyric poetry, in which the “I” shares with the others that enunciative centrality which had long been its exclusive prerogative.
Keywords: Raboni; Sixties; Lyric Poetry; I; Characters.